THE ETHNOBOTANY OF SENSE DISEASE MEDICAL PLANT USED BY NGIS MANGGIS COMMUNITY KARANGASEM IN BALI, INDONESIA - Dewa Ayu Sri Ratnani; I Ketut Junitha; Eniek Kriswiyanti; Desak Nyoman Budiningsih (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2022)
The Ngis Manggis community has ethnobotanical knowledge in utilizing plants from the forest for traditional medicine. Local people have little knowledge of managing forests sustainably. This study aimed to identify plants used for sense disease medicinal by the Ngis Manggis community, including species, family, local names, parts of plants used, processing method, usage method, obtained sources, and the Index of Cultural Significance (ICS). Qualitative method to obtain data on the local names of plants used for the sense disease medicinal. Purposive and Snowball sampling methods were applied to collect key informants through semi-structured interviews and moderate participation. Data analysis was qualitative and quantitative. The results showed that 55 species were distributed in 32 families to treat 17 diseases dominated by Fabaceae (6 species). Most of them were harvested from wild 29 (52.72%). The most widely used part of the plants is the leaf. Crushing is the most widely used preparation method by the community. The greatest number of medicinal uses of Ngis Manggis community is smeared. Based on the results of the ICS analysis, the highest ICS value is Arenga pinnata L. (61).